The influence of personality competence, social competence, and professional competence of school principals on teacher performance in Kopang District, Central Lombok - Marhamah, Saidati; Werang, Basilius Redan; Ariawan, I Putu Wisna (International research journal of management, IT and social sciences, 2025)
The purpose of this study was to analyze and describe the influence of the variables of personality, social, and professional competence of the principal on teacher1performance. This study was ex-post-facto on teachers of Public Elementary Schools in Kopang District, Central Lombok. The population of this study was 314 teachers spread across 47 schools. The research sample of 173 people was determined through the Isaac and Michael formula developed by Sugiyono. The data collection technique used a questionnaire and the analysis method was simple regression, multiple regression using the SPSS application. The results were; (1) Personality competence a very significant influence on teacher performance as evidenced by the regression equation Y = 32.161 + 1.072X1 correlation coefficient 0.204 and SE 14.52%. (2) Social competence a very significant influence on teacher performance evidenced by the regression equation Y= 26.448+1.590X2 correlation coefficient 0.439 and SE 37.72% (3) Professional competence has a very significant influence on teacher performance as evidenced by the regression equation Y= 20.777+1.295X3 correlation coefficient 0.343 and SE 29.46% (4) Simultaneously personality, social and professional have a very significant influence on teacher performance as evidenced by regression equation Y= -0.755+0.307X1+0.812X2+0.517X3 correlation coefficient 0.904 results from F-Count 251.733 and SE 81.70%.